2022
DOI: 10.3390/ijms231911506
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and Phenotype Differences in CADASIL from an Asian Perspective

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a hereditary cerebral small-vessel disease caused by mutations in the NOTCH3 gene. Classical pathogenic mechanisms are associated with cysteine gain or loss, but recent studies suggest that cysteine-sparing mutations might have a potential role as a pathogen. In comparison with CADASIL patients in Western countries, there are several differences in Asian patients: (1) prevalent locus of NOTCH3 mutations (exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…[ 8 ] Similarly, most of the NOTCH3 variants detected in this study were between exons 2 and 24. However, recent studies have reported that mutations between exons 25 and 33 may also cause CADASIL,[ 13 ] and we detected four variants in exons 25, 31, and 33. Two of these, L1518M and P2249P, were benign and likely benign, respectively, according to ACMG.…”
Section: Discussionmentioning
confidence: 45%
“…[ 8 ] Similarly, most of the NOTCH3 variants detected in this study were between exons 2 and 24. However, recent studies have reported that mutations between exons 25 and 33 may also cause CADASIL,[ 13 ] and we detected four variants in exons 25, 31, and 33. Two of these, L1518M and P2249P, were benign and likely benign, respectively, according to ACMG.…”
Section: Discussionmentioning
confidence: 45%
“…Previous reports have frequently identified NOTCH3 variants in exons 2-6, particularly exon 4 [Almeida et al, 2022;Kim et al, 2022]. In a study conducted in the United Kingdom, evaluating 200 symptomatic individuals, exon 4 variants were reported in 71.4% of the cases [Adib-Samii et al, 2010].…”
Section: Discussionmentioning
confidence: 96%
“…AM, known for its ability to induce vasodilation and lower blood pressure [7] , may theoretically worsen cerebral hypoperfusion and infarcts. The angiogenic properties of AM may raise concerns about an increased risk of cerebral hemorrhage, which is a common manifestation of CADASIL, particularly in East Asian populations [43] . Although our preclinical experiments with mice overexpressing AM in the systemic circulation have shown restoration of CBF without any damaging effects on the brain, the safety of AM in patients should be confirmed through clinical trials.…”
Section: Discussionmentioning
confidence: 99%